Flow Synthesis of Biologically-Relevant Compound Libraries - Luque Navarro, Pilar María (Molecules, 2020)
Flow chemistry is one of the most prominent enabling technologies that has greatly shaped the way chemists’ approach organic synthesis. Specifically, in drug discovery, the advantages of flow techniques over batch procedures allow the rapid and efficient assembly of compound libraries to be tested for biological properties. The aim of the present review is to comment on some representative examples from the last five years of literature that highlight how flow procedures are becoming of increasing importance for the synthesis of biologically-relevant molecules.